The Financial Management Assistance on Melijo Business Owners - Jariah, Ainun (IMPOWERMENT SOCIETY, 2021)
The activity aims to provide financial management assistance on melijo business owners in Biting village Kutorenon Sukodono, so that the business owners are able to improve their human resources skill to manage their business; strengthen the human resources skill in bookkeeping regularly and correctly; improve the ability in separating between business and household finances; and to find easy capital access. The method of community service activity has several stages, including the initial survey, the interview to find the offered problems and solutions, business management assistance, finance management, and operational aid for melijo business owners. The partner weakness mainly lies in the limited ability of human resources in managing their business, not yet available human resources who understand about bookkeeping trade business regularly; not yet separate business and household finances and limited capital access. The targets to be achieved, including: the improvement of partners skills in running their business in sustainable manner; strengthening partners skill in bookkeeping regularly and correctly; the improvement of partner skills in separating between business and household finances and easy capital access.